Breaking the frame: an analysis of strategic cognition and decision making under uncertainty - Hodgkinson, Gerard P.; Bown, Nicola J.; Maule, A. John; Glaister, Keith W.; Pearman, Alan (Strategic Management Journal, 1999)
This paper reports the findings of two experimental investigations into the efficacy of a causal cognitive mapping procedure as a means for overcoming cognitive biases arising from the framing of strategic decision problems. In Study 1, final year management studies undergraduate students were presented with an elaborated strategic decision scenario, under one of four experimental conditions: positively vs. negatively framed decision scenarios, with prechoice vs. postchoice mapping task orders (i.e., participants were required to engage in cognitive mapping before or after making a decision). As predicted, participants in the postchoice mapping conditions succumbed to the framing bias whereas those in the prechoice mapping conditions did not. Study 2 replicated and extended these findings in a field setting, on a sample of senior managers, using a decision scenario that closely mirrored a strategic dilemma currently facing their organization. Taken together, the findings of these studies indicate that the framing bias is likely to be an important factor in strategic decision making, and suggest that cognitive mapping provides an effective means of limiting the damage accruing from this bias. Copyright © 1999 John Wiley & Sons, Ltd.